Voltage source up to 30 kV with pulsation not more than 0.1% - Krivonosov, G.A.; Svystunov, O.А.; Vasiliev, A.V.; Sotnikov, G.V. (Problems of Atomic Science and Technology, 2023)
A DC source with a voltage of 30 kV with a ripple of less than 0.1% has been developed and manufactured for accelerating and focusing electrons in a dielectric laser accelerator on a chip structure. The source, which has a smooth voltage change limit from 10 to 30 kV, with a ripple of 0.1% over the entire voltage range in the specified range, is made on the basis of a 3-phase network. Such voltage stability is necessary for the correct recording of the energy of electrons accelerated by a laser pulse.